Eksplorasi kesalahan siswa kelas X dalam menyelesaikan soal eksponen dan logaritma berdasarkan kategori Watson - Nurhayati, Ani; Prabawanto, Sufyani; Novianingsih, Khusnul (IKIP Siliwangi, 2026)
The high level of students’ errors in solving problems on exponents and logarithms indicates the presence of conceptual difficulties that need to be analyzed systematically. This study aims to analyze high school students’ errors on exponents and logarithms. The research was conducted on tenth-grade students at a senior high school in Bandung, involving 20 students, from which 6 samples were randomly selected. This study employed a qualitative approach with a descriptive method. The research instrument consisted of validated exponent and logarithm problems. The results showed that, based on the percentage of students’ errors in solving mathematical problems according to Watson’s error categories, inapproriate procedure errors were classified as high, reaching 48%. Omitted data errors were categorized as low at 14%, and response level conflict errors were also categorized as low at 10%. Skill hierarchy errors were classified as very low at 5%. Errors outside the seven categories were categorized as low at 24%. Meanwhile, incorrect data errors, omitted conclusion errors, amd undirected manipulation errors were not found (0%), thus falling into the very low category.